Tok Pulau Manis: Pioneer of Fiqh writings in the Malay Peninsular - Zurita, Mohd Yusoff; Hasanulddin, Mohd; Engku Ibrahim, Engku Wok Zin (Canadian Center of Science and Education, 2015)
The proselytising of Islam in the Malay Peninsular depended on the earnestness of the classical Islamic scholars. The spreading of Islam was done through religious talks, Islamic studies classes, and through their writings. Syeikh Abdul Malik bin Abdullah, also known as Tok Pulau Manis is one of the classical Islamic scholars that was born in the state of Terengganu, which was active in producing religious books especially in the field of fiqh and taṣawwuf. However, most of the recent generations are not aware of his legacy and contributions in the spreading of Islam. Therefore, this article attempts to study his life and academic background, and highlights his contribution as one of the earliest classical Islamic scholars that produced fiqh writings in the Malay Peninsula. The result of this study finds that Tok Pulau Manis is an esteemed scholar, which was hold in high regard by the dignitaries including the Sultan Zainal Abidin I himself. His involvement in producing fiqh writings in Jāwī during the 17 and 18th century had placed him as one of the pioneers of the fiqh writing in the Malay Peninsula.